Locating giant ground pangolins (Smutsia gigantea) using camera traps on burrows in the Dja Biosphere Reserve, Cameroon - Bruce, T.; Kamta, R.; Mbobda, R.B.T.; Kanto, S.T.; Djibrilla, D.; Moses, I.; Deblauwe, V.; Njabo, K.; LeBreton, M.; Ndjassi, C.; Barichievy, C.; Olson, D. (SAGE Publications, 2018)
Giant ground pangolins (Smutsia gigantea) are poorly known and difficult to study due to their nocturnal and burrowing habits. Here, we test the efficacy of using camera traps on potentially active burrows identified by local Ba'Aka guides to rapidly locate giant ground pangolins in the wild for subsequent observation and tagging for telemetry studies. We deployed nine cameras on potential giant ground pangolin burrows in the Dja Biosphere Reserve, Cameroon. One camera photographed an adult male giant ground pangolin using a burrow within 2 days of camera deployment. The pangolin used the same burrow several times over a 25-day period and possible scent-marking behavior was recorded.